2018
DOI: 10.1088/1748-0221/13/03/p03018
|View full text |Cite
|
Sign up to set email alerts
|

Hadronic vs. electromagnetic pulse shape discrimination in CsI(Tl) for high energy physics experiments

Abstract: A: Pulse shape discrimination using CsI(Tl) scintillators to perform neutral hadron particle identification is explored with emphasis towards application at high energy electronpositron collider experiments. Through the analysis of the pulse shape differences between scintillation pulses from photon and hadronic energy deposits using neutron and proton data collected at TRIUMF, it is shown that the pulse shape variations observed for hadrons can be modelled using a third scintillation component for CsI(Tl), in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 31 publications
4
28
0
Order By: Relevance
“…Following the initial pre-amplification stage, the two signals are summed then processed by a CR-(RC) 4 shaping amplifier with shaping time of 0.5 µs [14]. The signal is then digitized into 31 samples with 18-bit precision and at a sample frequency of 1.7669 MHz (sample time of 0.56594 µs).…”
Section: Pulse Shape Discrimination With the Belle II Calorimetermentioning
confidence: 99%
See 4 more Smart Citations
“…Following the initial pre-amplification stage, the two signals are summed then processed by a CR-(RC) 4 shaping amplifier with shaping time of 0.5 µs [14]. The signal is then digitized into 31 samples with 18-bit precision and at a sample frequency of 1.7669 MHz (sample time of 0.56594 µs).…”
Section: Pulse Shape Discrimination With the Belle II Calorimetermentioning
confidence: 99%
“…To characterize the waveform pulse shape the techniques developed in reference [4] are applied. The study in reference [4] demonstrated that energy deposits by highly ionizing particles produce a CsI(Tl) scintillation component measured to have a decay time of 630 ± 10 ns.…”
Section: Pulse Shape Discrimination With the Belle II Calorimetermentioning
confidence: 99%
See 3 more Smart Citations